Boosting International Humanitarian Law Active Class Participation; Lesson Learned from Blended Learning Policy (Kemendikbud Circular No.4 2020) - Afandi Sitamala; Danial Danial (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
University is required to adapt the teaching method, creativity, and innovation during the covid outbreak. The learning method used in Learning Management System (LMS) is mixed with online methods by utilizing both synchronous and asynchronous multimedia. This study developed into several steps; the first step is identifying the problem in class participation before applying LMS and comparing it with the class participation afterward. Problem identification is carried out with a learning survey currently being carried out at the International Humanitarian Law class in Universitas Sultan Ageng Tirtayasa while applying mobile LMS to enhance class participation. Untirta's bold LMS (SPADA Untirta) can be upgraded to a more practical level by implementing SPADA mobile LMS applications as a valuable embodiment of LMS;